|x - 1| + 3x = 1
<=> |x - 1| = 1 - 3x (1)
ĐK : \(1-3x\ge0\Rightarrow x\le\frac{1}{3}\)
Khi đó (1) <=> \(\orbr{\begin{cases}x-1=1-3x\\x-1=3x-1\end{cases}}\Leftrightarrow\orbr{\begin{cases}4x=2\\2x=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{2}\left(\text{loại}\right)\\x=0\left(tm\right)\end{cases}}\)
Vậy x = 0
\(\left|x-1\right|+3x=1\)
\(\Leftrightarrow\left|x-1\right|=1-3x\left(ĐK:x\le\frac{1}{3}\right)\)
\(\Leftrightarrow\orbr{\begin{cases}x-1=1-3x\\x-1=3x-1\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x+3x=1+1\\x-3x=1-1\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}4x=2\\-2x=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{2}\left(KTMĐK\right)\\x=0\left(TMĐK\right)\end{cases}}\)
Vậy \(x=0\)
\(\left|x-1\right|+3x=1\Leftrightarrow\left|x-1\right|=1-3x\)
ĐK : \(x\le\frac{1}{3}\)
TH1 : \(x-1=1-3x\Leftrightarrow4x=2\Leftrightarrow x=\frac{1}{2}\)(ktm)
TH2 : \(x-1=3x-1\Leftrightarrow2x=0\Leftrightarrow x=0\)(tm)